Building Community-Based Economy At Neighborhood (RT) Level Through People’s Business And Digital Sales: Implementation Study Of WarungRakyat Application - Diky Firdaus; Hery Derajad Wijaya; Sabar Rudiarto; Andyan Pradipta Utama; Joko Sugiharjo; Loeky Rono Pradopo (Dinasti International Journal of Education Management and Social Science, 2025)
This study explores the integration of communal values, physical shelf arrangement (basket marketing), and digital technology through the WarungRakyat application to empower the neighborhood-level economy (RT). Using mixed methods, including surveys, focus group discussions, and Apriori algorithm analysis, this study was conducted in two RTs in Meruya Selatan, Jakarta Barat. The results indicate that the application improved business efficiency and product visibility. Community collaboration (gotong royong) strengthened logistics and participation. The study offers an integrative empowerment model aligned with the SDGs.